Pharmacokinetics of [18F]fleroxacin in healthy human subjects studied by using positron emission tomography. - Fischman, A J (1993)
Positron emission tomography (PET) with [18F]fleroxacin was used to study the pharmacokinetics of fleroxacin, a new broad-spectrum fluoroquinolone, in 12 healthy volunteers (9 men and 3 women). The subjects were infused with a standard therapeutic dose of fleroxacin (400 mg) supplemented with approximately 20 mCi of [18F]fleroxacin. Serial PET images were made and blood samples were collected for 8 h, starting at the initiation of the infusion. The subjects were then treated with unlabeled drug for 3 days (400 mg/day). On the fifth day, infusion of radiolabeled drug, PET imaging, and blood collection were repeated. In most organs, there was rapid accumulation of radiolabeled drug, with stable levels achieved within 1 h after completion of the infusion. Especially high peak concentrations (in micrograms per gram) were achieved in the kidney (> 34), liver (> 25), lung (> 20), myocardium (> 19), and spleen (> 18). Peak concentrations of drug more than two times the MIC for 90% of Enterobacteriaceae strains tested (> 10-fold for most organisms) were achieved in all tissues except the brain and remained above this level for more than 6 to 8 h. The plateau concentrations in tissues (2 to 8 h, in micrograms per gram +/- standard error of the mean) of drug were as follows: brain, 0.83 +/- 0.032; myocardium, 4.53 +/- 0.24; lung, 5.80 +/- 0.48; liver, 7.31 +/- 0.33; spleen, 6.00 +/- 0.47; bowel, 3.53 +/- 0.74; kidney, 8.85 +/- 0.64; bone, 2.87 +/- 0.29; muscle, 4.60 +/- 0.33; prostate, 4.65 +/- 0.48; uterus, 3.87 +/- 0.39; breast, 2.68 +/- 0.11; and blood, 2.35 +/- 0.09. Concentrations of fleroxacin in tissue were similar in males and females, before and after pretreatment with unlabeled drug.